Shame in Pastoral Practice: Reflections in the Light of Field Research, Bonhoeffer and Godly Play. Issue 4 (1st October 2016) - Nash, Sally
Abstract : Shame can be an immensely debilitating experience for some and the church as an institution does, at times, exacerbate this shame. This article draws on a qualitative research project exploring shame in the church in the light of ministerial praxis completed as part of ordination and post-ordination training. Two conversation partners illuminate a discussion of pastoral practice in relation to shame. Firstly Bonhoeffer's incomplete essay written in prison on what it means to tell the truth and secondly Godly Play's open, non-directive wondering questions. Truth telling is seen by Bonhoeffer as contextual and living rather than absolute and static in nature. It is also limited by constraints of time, place, mission and office or role. Wondering questions contribute to a pastoral approach which can help to mitigate against shaming and which resonate with Bonhoeffer's understanding of telling the truth. The intention of the article is to encourage a more mindful approach to pastoral practice in the light of an understanding of shame and how to work with those who have experienced it.